Bronchoscopic evaluation of unexplained recurrent and persistent pneumonia in children. Issue 3 (26th February 2013) - Gokdemir, Yasemin; Cakir, Erkan; Kut, Arif; Erdem, Ela; Karadag, Bulent; Ersu, Refika; Karakoc, Fazilet
<x xml:space="preserve">Abstract</x> Background Persistent or recurrent pneumonia in children can pose a significant challenge to paediatricians and respiratory physicians. Aim The aim of this study is to determine the role of flexible bronchoscopy (FB) in evaluation of recurrent or persistent pneumonia that remain otherwise unexplained by non‐invasive diagnostic tests in children. Methods Retrospective evaluation of patients who underwent FB with an indication of recurrent or persistent pneumonia from 1997 to 2011. Results Among 2600 FB procedures, 434 (17%) were performed with the indication of recurrent or persistent pneumonia. There were 237 (54%) boys. Median age at presentation was 84 months, and median duration of symptoms was 9 months. FB led to specific diagnosis in 33% of the cases. The most common diseases diagnosed by FB were malacia disorders (n: 32, 7%), aspirated foreign body (n: 30, 7%), endobronchial tuberculosis (n: 20, 5%), congenital airway anomalies (n: 14, 3%), mucus plugs (n: 14, 3%), pulmonary haemosiderosis (n: 12, 3%) and middle lobe syndrome (n: 11, 3%). During FB, only 6% of the patients had minor complications such as transient hypoxia, stridor and tachycardia. Conclusions In our study, FB proved to be a safe and effective tool in evaluation of children with persistent or recurrent pneumonia. FB is indicated for children with recurrent or persistent pneumonia where the underlying diagnosis remains unclear even after non‐invasive diagnostic tests.